Associations between knee pain and knee-loading physical activities at work and leisure – a cross-sectional study based on accelerometer measurements - Margareta Törnblom; Emma Haglund; Ann Bremander; Anna Nilsdotter; Maria LE Andersson; Pasan Hettiarachchi; Peter J Johansson; Magnus Svartengren; Katarina Aili (BMC Musculoskeletal Disorders)
Abstract Background Knee pain is often an early sign of knee osteoarthritis (KOA). Physical activities (PA) constitute the recommended regime to those affected. However, knee-loading PA at work is linked to an increased risk for KOA. The primary aim of this study was to investigate associations between knee pain and accelerometer-measured knee-loading PA, at work and leisure respectively. The secondary aim was to investigate knee-related problems in relation to self-reported physical effort at work. Methods This cross-sectional study included 107 working participants (aged 30–67) with knee pain. Knee pain was evaluated using the Knee Injury and Osteoarthritis Outcome Scale (KOOS), subscale Pain. Knee-loading PA (including daily steps, time in upright position, stair walking), and sitting/lying were measured by accelerometer for one week. Each knee-loading PA was analysed separately for the measurement periods: (1) total period, (2) time at work, and (3) leisure on workdays. Knee-related problems were evaluated by the KOOS subscales Symptoms, Activities of Daily Living, Function in Sport and Recreation, and Quality of Life. Analyses were made with linear regression, and stratified by high or low self-reported physical effort at work. Results Participants with more knee pain walked on average fewer steps per day, and spent less time in an upright position during leisure on workdays, unstandardized coefficient (β) = 0.001, p = 0.044, β = 0.075, p = 0.001 respectively, i.e. spent less time in knee-loading PA. The associations were stronger for those reporting high physical effort at work, β = 0.116, p = 0.016. Participants with high physical effort at work rated their (knee-related) quality of life worse. There were no associations between knee pain and knee-loading PA during work hours. Conclusions Participants with more knee pain were less physically active during leisure, with stronger associations among those with higher physical effort at work. Those reporting high physical effort at work had worse (knee-related) quality of life compared to participants reporting low effort at work. This highlights the importance of taking knee-loading PA at work and leisure into account when recommending exercise regimes to individuals with knee pain. Trial registration ClinicalTrials.Gov (NCT04928170), Date of registration: 2017-12-20.